Persepsi dan opini publik atas tayangan sinetron bernuansa pedofilia di indosiar - Henny Damaryanti; Klara Dawi Dawi; Yenny Aman Serah; Siswadi Siswadi; Temmy Hastian (Jurnal Komunikasi Profesional, 2022)
Zahra-related issues have received a lot of attention in early June 2021, with over 20,000 tweets. “Suara Hati Istri: Zahra” as one of Indonesia's leading soap operas that put Zahra as the main character has been criticized for promoting pedophilia. “Suara Hati Istri: Zahra” is also seen as a soap opera that encourages polygamy, pedophilia, and child marriage. Responding to the soap opera “Suara Hati Istri: Zahra” which aired on Indosiar, protests ensued. As a trigger, one of the actors Lea Chiarachel who is still 14 years old can play the third wife in the soap opera. They were punished not only because of their marital status, but also for showing scenes like husband and wife in soap operas. The purpose of this study is to find out how public opinion is on Indosiar pedophile soap operas. This study uses a quantitative approach with content analysis method in viewing tweets with the hashtag # Suarahatiistrizahra. The results of this study indicate that public opinion on the Indosiar pedophile soap opera with the hashtag # Suarahatiistrizahra is dominated by negative message content.